Sudan type lithium-sodium separation resin as well as preparation method and application thereof
Through the preparation of Sudan-type lithium-sodium separation resin, the use of Sudan functional groups to efficiently adsorb lithium ions in a high-concentration impurity ion environment, solving the problems of insufficient selectivity and poor stability of lithium-sodium separation resin, and achieving efficient and environmentally friendly lithium ion separation effect .
Patent Information
- Application Number
- CN202411601202.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-01-17
AI Technical Summary
The existing lithium sodium separation resins are insufficiently selective and have poor stability in high concentration impurity ion environments, which makes it difficult to separate lithium ions from sodium ions. The traditional methods are costly, complex in operation and harmful to the environment.
The preparation method of Sudan type lithium sodium separation resin is adopted, and the Sudan functional groups are introduced through chloromethylation and functionalization reactions to form a stable complex to efficiently adsorb lithium ions, and the chemical stability of the resin is improved through specific preparation steps and Mechanical strength.
It realizes high selective adsorption of lithium ions in a high sodium ion environment, improves the recovery and purity of lithium ions, and has good chemical stability and mechanical strength, which is suitable for industrial-scale lithium-sodium separation process.
Smart Images

Figure CN119320470A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a Sudan type lithium sodium separation resin and a preparation method and application thereof, belonging to the technical field of resin materials. Background Art
[0002] The technical background of lithium-sodium separation resin is mainly aimed at the challenges faced by the extraction and purification process of lithium resources in the lithium-ion battery industry. With the rapid development of electric vehicles and renewable energy storage systems, the global demand for high-purity lithium has risen sharply. However, in the process of lithium extraction, separating lithium from lithium-containing solutions (such as lithium precipitation mother liquor, electrodialysis tail liquor, etc.) and removing impurities, especially sodium with similar chemical properties to lithium, has always been a technical problem. Traditional separation methods include chemical precipitation, solvent extraction, etc., but these methods are often costly, complicated to operate, and have a certain impact on the environment. Therefore, the development of an efficient, environmentally friendly and economical lithium-sodium separation technology has become an important demand in the industry.
[0003] Lithium-sodium separation resins usually carry specific functional groups, which play a key role in improving the adsorption selectivity and adsorption capacity of lithium ions. In the synthesis of lithium-sodium separation resins, researchers are committed to improving the selectivity and adsorption capacity of lithium ions by introducing specific functional groups. The following are some common lithium-sodium separation resins and the functional groups they may contain: Nitrogen-containing functional groups: such as amino (-NH2), imino (=NH) and quaternary ammonium (-NR3 + ), these functional groups can form complexes with lithium ions through electrostatic attraction, thereby improving the adsorption efficiency of lithium ions. Oxygen-containing functional groups: such as hydroxyl (-OH), carboxyl (-COOH) and sulfonic acid (-SO3H), these functional groups can undergo coordination exchange with lithium ions, thereby effectively adsorbing lithium ions. Phosphorus-containing functional groups: such as phosphate (-PO3H2), this type of functional group has a strong affinity for multivalent metal ions and can be used to improve the selectivity of lithium.
[0004] The disadvantages of the functional groups commonly used in the synthesis of lithium-sodium separation resins mainly include insufficient selectivity, low adsorption efficiency, and poor stability under certain environments. Although the nitrogen-containing, oxygen-containing, and phosphorus-containing functional groups commonly used in the synthesis of lithium-sodium separation resins can form complexes with lithium ions through electrostatic attraction or coordination exchange and effectively adsorb lithium ions, they are usually sensitive to environmental conditions such as pH value, ionic properties, etc. This leads to a significant decrease in the performance of these functional groups in actual use, especially under complex feed solution compositions and changing environmental conditions, affecting the recovery rate and purity of lithium. In addition, these functional groups may not have sufficient stability, especially in high-concentration salt lake lithium extraction environments, where they may be degraded by chemical or physical effects, thereby reducing the service life of the adsorbent.
[0005] Lithium-sodium separation resins usually contain specific functional groups that are responsible for the adsorption and desorption of lithium ions. However, these functional groups may have some defects that affect the overall performance of the lithium-sodium separation resin. The shortcomings of these functional groups and related improvement measures are discussed in detail below. Chemical stability: In some chemical reactions, the functional groups may undergo unnecessary side reactions with other components in the solution, resulting in a decrease in the adsorption performance of the resin. Poor selectivity: Some functional groups may have insufficient recognition of lithium and sodium ions, resulting in these two ions being easily misadsorbed or released during the separation process. Limited adsorption capacity: The number and type of functional groups may limit the adsorption capacity of the resin, making it difficult to achieve efficient selective adsorption of lithium ions in complex solutions. Poor water resistance: Some functional groups may not be water-resistant, which may cause the functional groups of the resin to fall off after long-term use, thereby affecting the service life and separation efficiency of the resin. Summary of the invention
[0006] The purpose of the present invention is to introduce Sudan-type lithium ion selective functional groups to highly selectively adsorb lithium ions in a solution in the presence of high concentrations of impurity ions, thereby solving the problem of difficulty in separating lithium ions from impurity ions such as sodium ions, potassium ions and magnesium ions during lithium extraction from salt lakes.
[0007] The technical solution adopted by the present invention to achieve the above-mentioned purpose is:
[0008] The present invention provides a method for preparing a Sudan-type lithium-sodium separation resin, comprising the following steps:
[0009] (1) Chloromethylation reaction: the resin balls, organic solvent, carboxymethyl cellulose, chloromethylation agent and catalyst are mixed and stirred, and then the chloromethylation agent is added dropwise again during heating to carry out chloromethylation reaction, and then the mixture is steamed to obtain dry resin balls;
[0010] (2) Functionalization reaction: resin chlorine balls, nitrogen-containing organic aqueous solution, dispersant carboxymethyl cellulose solution, Sudan or Sudan derivatives and chloroacetic acid are mixed, heated and continuously stirred to carry out functionalization reaction;
[0011] (3) Product separation and purification: After the functionalization reaction is completed, centrifugation, filtration and washing are performed to obtain functionalized resin microspheres, which are then dried under vacuum conditions to obtain Sudan-type lithium sodium separation resin.
[0012] Furthermore, the step of mixing and stirring the resin white balls, organic solvent, carboxymethyl cellulose, chloromethylation agent and catalyst in step (1) comprises: adding the polystyrene resin white balls into the organic solvent at room temperature, and adding carboxymethyl cellulose and chloromethylation agent, soaking and stirring for 1 to 2 hours, then adding the catalyst, and continuing to stir for 1 to 2 hours.
[0013] Furthermore, the step of adding the chloromethylation reagent again during the heating process in step (1) comprises: heating to 43-65° C., keeping the temperature for 6-10 hours, adding the chloromethylation reagent again during this process, adding the reagent again over 1-2 hours, and maintaining the reaction temperature at 43-65° C.
[0014] Furthermore, the step of steaming treatment in step (1) comprises: firstly adding a stirring medium, heating to evaporate the chloromethylation agent, then cooling and filtering to dry, collecting the mother liquor, washing the generated resin chlorine balls with water until the washing liquid is neutral, and drying under reduced pressure at 40 to 45° C. for 4 to 6 hours to obtain dry resin chlorine balls.
[0015] Furthermore, the material of the resin white balls in step (1) is polystyrene resin or polystyrene resin.
[0016] Furthermore, in step (1), the organic solvent is petroleum ether.
[0017] Furthermore, in step (1), the chloromethylation reagent is biphenyl dichlorobenzyl (BCMB).
[0018] Furthermore, in step (1), the catalyst is selected from one of tin tetrachloride, zinc chloride and ferric chloride.
[0019] Furthermore, in step (2), the resin chloride balls, the nitrogen-containing organic aqueous solution, the dispersant carboxymethyl cellulose solution and Sudan or Sudan derivatives are first mixed, the mixed solution is heated to 55-65° C., and then chloroacetic acid is added, and the reaction is continuously stirred for 18-24 hours.
[0020] Furthermore, the nitrogen-containing organic aqueous solution in step (2) is selected from a hydrazine hydrate aqueous solution or an aqueous solution of a matrix material containing azodioxide.
[0021] The present invention also provides a Sudan type lithium sodium separation resin, which is prepared by the above preparation method. The structural formula of the Sudan type lithium sodium separation resin is:
[0022]
[0023] Wherein, R1, R2, R3, and R4 appear alone or in combination, wherein R1 is -CH3, One of the following; R2 is -OCH3; R3 is -CH3; R4 is -OH.
[0024] Furthermore, the core functional group structure of the Sudan-type lithium sodium separation resin is Specifically, any of the following:
[0025]
[0026] The present invention also proposes the use of Sudan-type lithium-sodium separation resin in electrodialysis tail liquid or lithium precipitation mother liquid for separating lithium ions and sodium ions in the solution.
[0027] The present invention has achieved the following beneficial effects:
[0028] (1) The Sudan type lithium sodium separation resin prepared by the present invention is based on a matrix of styrene or its copolymer, and this matrix has good chemical stability and mechanical strength.
[0029] (2) The Sudan type lithium sodium separation resin prepared by the present invention carries Sudan functional groups. Sudan (phenylazonaphthol) as an organic ligand contains unique nitrogen and oxygen coordination atoms in its molecular structure, which can form a stable complex with lithium ions. At the same time, lithium ions, as a small positively charged metal ion, have a strong affinity for coordination atoms containing lone pairs of electrons. Therefore, the Sudan functional group can form a stable coordination bond with lithium ions, can efficiently adsorb lithium ions, thereby achieving specific adsorption of lithium ions, while the adsorption of sodium ions is relatively weak. Lithium ions can be specifically adsorbed and separated in a high sodium ion environment, which can solve the problem of difficulty in separating lithium ions from impurity ions such as sodium ions in complex systems.
[0030] (3) The Sudan-type lithium sodium separation resin prepared by the present invention presents a small particle form with uniform size, which helps to improve its mass transfer efficiency and stability in the liquid medium, and has a high adsorption capacity, which is enough to adsorb a large amount of lithium ions.
[0031] (4) The Sudan-type lithium-sodium separation resin prepared by the present invention has a moderate moisture content ratio, which helps to maintain its moist state during operation and avoid volume changes caused by excessive water absorption.
[0032] (5) The Sudan-type lithium-sodium separation resin prepared by the present invention has excellent stability and durability and is suitable for industrial-scale lithium-sodium separation processes. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a diagram of the steps for preparing the Sudan-type lithium-sodium separation resin prepared in Example 1.
[0034] Figure 2 The synthetic route of Sudan type lithium sodium separation resin prepared in Example 1 is shown in FIG.
[0035] Figure 3 This is a finished product picture of the Sudan type lithium sodium separation resin prepared in Example 1.
[0036] Figure 4 It is a graph showing the lithium adsorption capacity of the Sudan-type lithium-sodium separation resin prepared in Example 1 in the electrodialysis tail liquid.
[0037] Figure 5It is a graph showing the lithium adsorption capacity of the Sudan-type lithium-sodium separation resin prepared in Example 1 in a lithium precipitation mother liquor. DETAILED DESCRIPTION
[0038] In order to make the various technical features and advantages or technical effects in the above technical solutions of the present invention more obvious and easy to understand, they are described in detail below with reference to the accompanying drawings.
[0039] Example 1. Preparation of Sudan-type lithium sodium separation resin
[0040] Preparation process Figure 1 and Figure 2 As shown, the specific preparation steps are as follows:
[0041] (1) Chloromethylation reaction: At room temperature, add polystyrene resin white balls into petroleum ether and add carboxymethyl cellulose and diphenylbenzyl chloride, soak and stir for 1 hour, then add catalyst (tin tetrachloride) and continue stirring for another 1 hour. The current operation allows the polystyrene white balls to fully contact with diphenylbenzyl chloride, making preliminary preparations for chloromethylation.
[0042] Then, the temperature was slowly raised to 43°C and kept for 6 hours. During this process, biphenyl dichlorobenzyl was added dropwise again, and the addition was completed within 1 hour, and the reaction temperature was kept at 43°C. This stage is the main part of the chloromethylation reaction, which introduces chloromethyl groups and ensures the efficiency of chloromethylation by precisely controlling temperature and time.
[0043] Then, the boiling treatment is carried out to recover and recycle part of the reactants and by-products. First, a stirring medium is added to heat up and distill out the biphenyl dichloride, then the temperature is lowered and filtered to collect the mother liquor, the resin chloride balls are washed with water until the washing liquid is close to neutral, and then dried under reduced pressure at 45°C for 4 hours to obtain dry resin chloride balls.
[0044] (2) Functionalization synthesis: Add the obtained resin chlorine ball to the hydrazine hydrate aqueous solution, add carboxymethyl cellulose and the functional group agent Sudan or Sudan derivative, then heat to 55°C and continuously add chloroacetic acid, and place in a rotary evaporator to react for 12 hours to carry out the functionalization reaction and introduce lithium selective functional groups. This stage is the main part of the functionalization reaction, and the functionalization efficiency is ensured by precisely controlling the temperature and time.
[0045] (3) Product separation and purification: After the reaction is completed, the modified microspheres are separated from the reaction system by centrifugation, filtration, etc., and washed with an appropriate solvent to remove unreacted chloromethylation reagents, functionalization reagents and other impurities. Finally, the functionalized resin microspheres are dried under vacuum conditions to obtain the final Sudan type polystyrene resin (i.e. Sudan type lithium sodium separation resin) product, such as Figure 3 Actual item shown.
[0046] Example 2. Preparation of Sudan-type lithium sodium separation resin
[0047] Preparation process Figure 1 and Figure 2 As shown, the specific preparation steps are as follows:
[0048] (1) Chloromethylation reaction: At room temperature, add polystyrene resin white balls into petroleum ether and add carboxymethyl cellulose and biphenyl dichloride, soak and stir for 1.5 hours, then add catalyst (tin tetrachloride), and continue stirring for 1.5 hours.
[0049] Then, the temperature was slowly raised to 55°C and kept at this temperature for 8 hours. During this process, biphenyl dichlorobenzyl was added dropwise again, and the addition was completed within 1.5 hours, and the reaction temperature was maintained at 55°C.
[0050] Then, the boiling treatment is carried out to recover and recycle part of the reactants and by-products. First, a stirring medium is added to heat up and distill out the biphenyl dichloride, then the temperature is lowered and filtered to collect the mother liquor, the resin chloride balls are washed with water until the washing liquid is close to neutral, and then dried under reduced pressure at 40°C for 6 hours to obtain dry resin chloride balls.
[0051] (2) Functionalization synthesis: Add the obtained resin chloride ball to the hydrazine hydrate aqueous solution, add carboxymethyl cellulose and the functional group agent Sudan or Sudan derivative, then heat to 60°C and continuously add chloroacetic acid, and place in a rotary evaporator to react for 18 hours.
[0052] (3) Product separation and purification: The operation is the same as in Example 1.
[0053] Example 3. Preparation of Sudan-type lithium sodium separation resin
[0054] Preparation process Figure 1 and Figure 2 As shown, the specific preparation steps are as follows:
[0055] (1) Chloromethylation reaction: At room temperature, add polystyrene resin white balls into petroleum ether and add carboxymethyl cellulose and biphenyl dichloride, soak and stir for 2 hours, then add catalyst (tin tetrachloride) and continue stirring for 2 hours.
[0056] Then, the temperature was slowly raised to 65°C and kept at this temperature for 10 hours. During this process, biphenyl dichlorobenzyl was added dropwise again, and the addition was completed within 2 hours, while the reaction temperature was kept at 65°C.
[0057] Then, the boiling treatment is carried out to recover and recycle part of the reactants and by-products. First, a stirring medium is added to heat up and distill out the biphenyl dichloride, then the temperature is lowered and filtered to collect the mother liquor, the resin chloride balls are washed with water until the washing liquid is close to neutral, and then dried under reduced pressure at 43°C for 5 hours to obtain dry resin chloride balls.
[0058] (2) Functionalization synthesis: Add the obtained resin chloride ball to the hydrazine hydrate aqueous solution, add carboxymethyl cellulose and the functional group agent Sudan or Sudan derivative, then heat to 65°C and continuously add chloroacetic acid, and place in a rotary evaporator to react for 24 hours.
[0059] (3) Product separation and purification: The operation is the same as in Example 1.
[0060] Example 4. Application of Sudan-type lithium sodium separation resin in electrodialysis tail liquid
[0061] Measure 100mL of dry Sudan-type lithium sodium separation resin (prepared by Example 1), and then fill the resin into the chromatographic column. Prepare 6L of electrodialysis tail liquid (composition see Table 1) and adjust the pH to 8.5; prepare 3.75L of deionized water and adjust the pH to 4.5. Use a peristaltic pump to pump the electrodialysis tail liquid / deionized water in from the top and out from the bottom. The adsorption phase time is 2h, 8BV (Bed volume) of brine is fed, and the cumulative brine feed is 400mL. The desorption phase time is 1.5h, 5BV of water is fed, and the cumulative water feed is 250mL. Repeat the above operation and conduct 15 cycles. After the adsorption and desorption are completed, the various components of the tail brine are tested. The test results are shown in Table 2. The lithium adsorption capacity data is shown in Table 2. Figure 4 The results show that in the 15 cycles of the test, the adsorption capacity of Sudan-type lithium-sodium separation resin was always maintained between 3.1 and 3.5 g / L, the impurity content was low and the sodium-to-lithium ratio was only 0.1:1, while the capacity of traditional resin in electrodialysis tail liquid was generally between 1.5 and 2 g / L, and the sodium-to-lithium ratio was as high as about 1.6:1. This experiment strongly illustrates the excellent performance of Sudan-type lithium-sodium separation resin.
[0062] Table 1. Electrodialysis tail liquid brine components of a salt lake enterprise in Qinghai
[0063] Components Li Na K Ca Mg B <![CDATA[SO4 2- ]]> Cl Concentration (g / L) 0.51 0.52 0.17 0.05 53.25 3.12 17.28 0.14
[0064] Table 2. Tail halogen composition of electrodialysis tail liquid after separation by Sudan type lithium sodium separation resin
[0065] Components Li Na K Ca Mg B <![CDATA[SO4 2- ]]> Cl Concentration (g / L) 1.28 0.11 0.01 Not detected 0.12 0.14 0.06 0.01
[0066] Example 5. Application of Sudan-type lithium sodium separation resin in lithium precipitation mother liquor
[0067] Measure 100mL of dry Sudan-type lithium sodium separation resin (prepared by Example 1), and then fill the resin into the chromatographic column. Prepare 1.5L of lithium precipitation mother liquor (composition see Table 3) and adjust the pH to 8.5; prepare 3.75L of deionized water and adjust the pH to 5.5. Use a peristaltic pump to pump the electrodialysis tail liquid / deionized water in from the top and out from the bottom. The adsorption phase time is 2h, the brine intake is 2BV (Bed volume), and the cumulative brine intake is 100mL. The desorption phase time is 1.5h, the water intake is 5BV, and the cumulative water intake is 250mL. Repeat the above operation and conduct 15 cycles of experiments. After the adsorption and desorption are completed, the various components of the tail brine are tested. The test results are shown in Table 4. The lithium adsorption capacity data is shown in Table 4. Figure 5 As shown. The results show that the resin of the present invention still maintains an adsorption capacity of lithium ions between 2.9 and 3.4 g / L in a harsh environment with a sodium-to-lithium ratio of 27.4:1, with very low content of other impurities and a sodium-to-lithium ratio of only 0.13:1, while the adsorption capacity of conventional resins in lithium precipitation mother liquor is generally between 1.1 and 1.6 g / L, with a sodium-to-lithium ratio of up to about 2.5:1. This experiment once again proves that the resin of the present invention still has high selectivity for lithium ions in an actual brine environment with high sodium ions.
[0068] Table 3. Composition of lithium precipitation mother liquor of a salt lake enterprise in Qinghai
[0069] Components Li Na K <![CDATA[CO3 2- ]]> Cl Concentration (g / L) 2.14 58.64 1.85 21.46 39.13
[0070] Table 4. Tail halogen composition of lithium precipitation mother liquor after separation by Sudan type lithium sodium separation resin
[0071] Components Li Na K <![CDATA[CO3 2- ]]> Cl Concentration (g / L) 3.29 0.44 0.02 0.96 1.21
[0072] Although the present invention has been disclosed as above by way of embodiments, it is not intended to limit the present invention. Appropriate modifications or equivalent substitutions of the technical solutions of the present invention made by ordinary technicians in the field should all be included in the protection scope of the present invention. The protection scope of the present invention shall be based on what is defined in the claims.
Claims
1. A method for preparing a Sudan-type lithium-sodium separation resin, characterized in that: The following steps are involved: (1) mixing and stirring resin balls, an organic solvent, carboxymethyl cellulose, a chloromethylation agent and a catalyst, then dropping the chloromethylation agent again during heating to carry out a chloromethylation reaction, and then steaming to obtain dry resin balls; (2) mixing resin chlorine balls, nitrogen-containing organic aqueous solution, dispersant carboxymethyl cellulose solution, Sudan or Sudan derivatives, and chloroacetic acid, heating and continuously stirring to carry out a functionalization reaction; (3) After the functionalization reaction is completed, centrifugation, filtration and washing are performed to obtain functionalized resin microspheres, which are then dried under vacuum conditions to obtain Sudan-type lithium-sodium separation resin.
2. The preparation method according to claim 1, characterized in that The step of mixing and stirring the resin white balls, organic solvent, carboxymethyl cellulose, chloromethylation agent and catalyst in step (1) comprises: adding the polystyrene resin white balls into the organic solvent at room temperature, adding carboxymethyl cellulose and chloromethylation agent, soaking and stirring for 1 to 2 hours, then adding the catalyst, and continuing to stir for 1 to 2 hours.
3. The preparation method according to claim 1, characterized in that: The step of adding the chloromethylation reagent again during the heating process in step (1) comprises: heating to 43-65° C., keeping the temperature for 6-10 hours, and adding the chloromethylation reagent again during this process, adding the reagent again over 1-2 hours, and maintaining the reaction temperature at 43-65° C.
4. The preparation method according to claim 1, characterized in that: The cooking step in step (1) comprises: firstly, adding a stirring medium, heating to evaporate the chloromethylation agent, then cooling to filter and dry, collecting the mother liquor, washing the generated resin chlorine balls with water until the washing liquid is neutral, and drying under reduced pressure at 40 to 45° C. for 4 to 6 hours to obtain dry resin chlorine balls.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The material of the resin white ball in step (1) is polystyrene resin or polystyrene resin; the organic solvent is petroleum ether; the chloromethylation reagent is biphenyl benzyl dichloride; and the catalyst is one of tin tetrachloride, zinc chloride and ferric chloride.
6. The preparation method according to claim 1, characterized in that: In step (2), the resin chloride balls, the nitrogen-containing organic aqueous solution, the dispersant carboxymethyl cellulose solution and Sudan or Sudan derivatives are first mixed, the mixed solution is heated to 55-65° C., and then chloroacetic acid is added, and the reaction is continuously stirred for 18-24 hours.
7. The preparation method according to claim 1 or 6, characterized in that: In step (2), the aqueous solution of nitrogen-containing organic matter is selected from an aqueous solution of hydrazine hydrate or an aqueous solution of a matrix material containing azodioxide.
8. A Sudan-type lithium-sodium separation resin prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The structural formula of the Sudan type lithium sodium separation resin is: Wherein, R1, R2, R3, and R4 appear alone or in combination, wherein R1 is -CH3, One of the following; R2 is -OCH3; R3 is -CH3; R4 is -OH.
9. The Sudan type lithium sodium separation resin according to claim 8, characterized in that The core functional group structure of the Sudan-type lithium sodium separation resin Specifically, any of the following:
10. Use of Sudan-type lithium-sodium separation resin prepared by the preparation method according to any one of claims 1 to 7 in electrodialysis tail liquid or lithium precipitation mother liquid, characterized in that: Used to separate lithium ions and sodium ions in solution.
Citation Information
Cited By
Resin for lithium extraction and preparation method and application thereof
CN119798509A